ANALISIS BIAYA MANFAAT PENGUSAHAAN SAPI PERAH DAN PEMANFAATAN LIMBAH UNTUK MENGHASILKAN BIOGAS PADA KONDISI RISIKO (Studi Kasus: Kecamatan Cisarua dan Megamendung, Kabupaten Bogor, Jawa Barat) - Nurmalina, Rita (Jurnal Pertanian, 2010)
The issue of energy crisis is one issue that developed in the world today. Indonesia has a national energy policy which aims to develop energy that can fulfill the needs of society as a cheap and affordable, one with biogas development. Dairy farm has a huge potential in renewable energy development. The largest population of dairy cattle in the District of Bogor there is in Cisarua and Megamendung Regency. The farmers already have a scale of 5 m3 of biogas installations with a total ownership of cow is 6 tails. Milk produced has a fluctuation in prices and production, so it needs to be studied further whether the business exploitation and utilization of dairy cow waste to produce instalation biogas 5 m3 scale is feasible to run both in normal conditions or in conditions of risk. The purpose of this research is to analyze non financial aspects like technical aspects; market aspects; aspects of management and social; and environmental aspects, analyze financially, and analysis of scenarios under conditions of price and production risk. The data described qualitatively and quantitatively. Results of non-financial analysis shows that this business is feasible to run. Financial analysis show the business is feasible because NPV Rp 82.401.004,07, Net B/C 2,20, IRR 23 percent, Payback Period 5 years 1 month and the business has a high level of risk on the condition of dairy production risk.